PENERAPAN METEODE CARD SORT UNTUK MENINGKATKAN KEAKTIFAN SISWA KELAS V PADA PELAJARAN AL QUR’AN HADITS - Salpiana, Salpiana; Husairi, Husairi (LP2M STAI Darul Kamal NW Kembang Kerang, 2022)
Abstract Based on observations, the educator's task in order to optimize the teaching and learning process is as a facilitator who is able to develop students' willingness to learn to achieve active and fun learning activities, the purpose of this research was conducted to increase student activity in the learning process. This research was designed using Classroom Action Research. The research instrument used in this research was an observation sheet and field notes used to obtain data or information relating to class situations that were not included in the observation sheet. In this study, field notes were used to observe things that happened in the classroom during the application of the card sort learning method. The results showed that in the first cycle the average student activity was in the less active category. Furthermore, in cycle II, the average student activity has shown the quite active category, however, in this cycle, improvements still need to be made so that researchers use cycle III. In cycle III, the average student activity has shown the active category. Thus, the Card Sort learning method can be recommended to teachers in carrying out learning.